Competency Assessment for State Highway Agency Project Managers. Issue 3 (March 2019) - Rezk, Sarah; Whited, Gary C.; Ibrahim, Michael; Hanna, Awad S.
Project managers (PMs) play a key role in the successful completion of construction projects. Therefore, PM competencies have been heavily investigated over the past few decades, often focusing on two types of skills: hard skills, including technical knowledge; and soft skills, including personal traits. This extensive body of knowledge was lacking the focus on PMs of transportation projects who work in a state highway agency (SHA). This research addresses this gap by developing a comprehensive competency assessment model tailored for SHA PMs. This research identified 55 PM essential competencies spanning five categories: project management knowledge and experience; leadership; SHA operational knowledge and experience; industry knowledge and experience; and cognitive/personal effectiveness. Also, by collecting extensive data from 90 PMs, this research developed a mathematical model to compute competency weights for differentiating exceptional and average PMs. The weights were then used to create a comprehensive score that can assess PM competencies as an overall percentage. This score was benchmarked using the collected data to distinguish between exceptional and average PMs. To effectively communicate the research findings to industry practitioners, a computer-based tool was created. This tool assists SHAs and their PMs in assessing competencies, and identifies training needs to improve overall PM performance and skill sets. The tool was tested and validated by five Wisconsin Department of Transportation PM supervisors, all of whom acclaimed its accuracy and potential value.